A comparative study on vascularization and the structure of the epidermis of an amphibious mudskipper fish, Scartelaos gigas (Gobiidae, Teleostei), on different parts of the body and the appendages. (27th September 2012) - Beon, M. S.; Oh, M. K.; Lee, Y. J.; Kim, C. H.; Park, J. Y.
Summary Epidermal structure of the amphibious mudskipper, Scartelaos gigas (Gobiidae), was investigated in relation to their terrestrial adaptation whereby a histological study on the epidermis of 15 regions including nine body regions, five fins and the sucking disc was carried out. The structure of the epidermis consists of three layers: an outermost layer with polygonal cells or rather flattened cells, small cells and mucous cells; a thick middle layer with voluminous cells swollen by epidermal cells; and the stratum germinativum. A dermal bulge was located at each apical area of the epidermis of almost all body regions, but was not existent in the operculum and the appendages, including none of the fins or the sucking disc. In the epidermis of the body regions, the dermal bulges had numerous dermal capillaries just beneath the stratum germinativum. By contrast, the appendages never had dermal capillaries due to the absence of the dermal bulge. Based on these results, the cutaneous air uptake in S. gigas would seem to be more effective in the upper body regions that are most often exposed to air than in the lower body regions, however, cutaneous air uptake is not likely to occur in the appendages.